2005
DOI: 10.1136/gut.2004.049460
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of lymphoma among inflammatory bowel disease patients treated with azathioprine and 6-mercaptopurine

Abstract: Background: Inflammatory bowel disease (IBD) is commonly treated with immunomodulators such as azathioprine and 6-mercaptopurine (6-MP). Studies examining lymphoma risk in IBD patients treated with these medications have been underpowered and have yielded conflicting conclusions. Aims: The purpose of this meta-analysis was to provide a more precise estimate of the relative risk of lymphoma among IBD patients treated with azathioprine or 6-MP. Methods: Studies were included if they were English language, full a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
452
1
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 735 publications
(478 citation statements)
references
References 21 publications
7
452
1
18
Order By: Relevance
“…Similarly, no preventive effect (HR, 1.06-1.3) of azathioprine/6-mercaptopurine use could be demonstrated during an 8-year follow-up in a more recent study [94] . Of note, azathioprine was reported to be associated with a 4-fold elevated risk of lymphomas in some previous studies [95] and a recent meta-analysis [96] . Although IBD itself was not associated with an increased risk for lymphoma [97] , disease severity cannot be excluded as a confounding variable.…”
Section: Chemoprevention In Ibd-is It Possible?mentioning
confidence: 99%
“…Similarly, no preventive effect (HR, 1.06-1.3) of azathioprine/6-mercaptopurine use could be demonstrated during an 8-year follow-up in a more recent study [94] . Of note, azathioprine was reported to be associated with a 4-fold elevated risk of lymphomas in some previous studies [95] and a recent meta-analysis [96] . Although IBD itself was not associated with an increased risk for lymphoma [97] , disease severity cannot be excluded as a confounding variable.…”
Section: Chemoprevention In Ibd-is It Possible?mentioning
confidence: 99%
“…67 Secondly, there is a fourfold documented increase in the risk of lymphoma with these medications which can present in the oral cavity. 68,69 It should be noted, however, that there is only a very small absolute increase in the risk of lymphoma occurrence.…”
Section: -Asasmentioning
confidence: 99%
“…22 Whether or not treatment with thiopurines increases the risk of lymphoma has long been debated, and a recent meta-analysis concluded that the risk of developing lymphoma increased fourfold in IBD patients on immunosuppressives. 23 However, the absolute risk is small and early introduction of immunosuppressive therapy is beneficial due to the decreased need for corticosteroids and better disease control.…”
Section: Immunosuppressivesmentioning
confidence: 99%